Investigating Factors Associated with Immunization Incompletion of Children Under Five in Ebonyi State, Southeast Nigeria: Implication for Policy Dialogue. (February 2021) - Umoke, Prince Christian Ifeanachor; Umoke, MaryJoy; Nwalieji, Chioma Adaora; Igwe, Festus Okechukwu; Umoke, Ugochi Georgina; Onwe, Rosemary N.; Nwazunku, Augustine Alugbala; Nwafor, Ifeanyi Emmanuel; Chukwu, Obinna Jude; Eyo, Nora; Ugwu, Adaeze; Ogbonnaya, Kalu; et al.
Purpose. To investigate factors associated with immunization incompletion of children under 5 years in Ebonyi state, Southeastern part of Nigeria. Method. A cross-sectional and a cluster sampling design were implemented; 400 women of childbearing age in families with children between 0 to 59 months of age were interviewed in Ebonyi state. Demographic characteristics of the child and mother, the child's immunization history, and reasons for partial immunization were obtained with the use of a self-administered questionnaire. Data were analyzed using descriptive statistics of mean, standard deviation, t -test and ANOVA with SPSS version 23 and hypothesis tested at P  < .05. Results . Findings revealed that 180 (48.1%) females, and 194 (51.9%) males' children were immunized; Less than half 155 (41.9%) of the children had 1 missed dose, considered as partial immunization cases indicating low coverage. Of the reasons given for incomplete immunization mothers, mothers agreed that immunization centers are far from home (x̄ = 2.55 ± 0.92). This reason significantly affects mothers who were young (≤20 years) ( x  = 2.86 ± 0.94; P  = .018), single ( x  = 2.84 ± 1.05; 0.037), had secondary education ( x  = 2.65 ± 1.08;0.000), students (2.89 ± 1.08; P  = .000), poor ( x  = 2.63 ± 1.05; P  = .009), and primiparous ( x  = 2.50 ± 1.08; P  = .036) are more affected and they agreed (grand mean >2.50). Conclusion. Immunization coverage was low, and far location from health facility was indicted thus policy implementers should locate health facilities close to homes. also health education on the importance of immunization should be given to mothers especially those who are young and has low socio-economic status.